Assessing the Rates, Predictors, and Complications of Blood Transfusion Volume in Posterior Arthrodesis for Adolescent Idiopathic Scoliosis - Minhas, Shobhit V; Chow, Ian; Bosco, Joseph; Otsuka, Norman Y (Spine (Philadelphia, Pa. 1976), 2015)
Retrospective cohort study. To determine predictors of and 30-day complications associated with blood transfusion volume after posterior spinal fusion for adolescent idiopathic scoliosis (AIS). Posterior arthrodesis is a common procedure performed for AIS, and patients frequently require perioperative blood transfusions. Few studies, however, have examined the rates and potential complications associated with blood transfusion volume. Patients undergoing posterior arthrodesis for AIS were selected from the National Surgical Quality Improvement Program pediatric database from 2012 to 2013. Patients were stratified on the basis of blood transfusion volume and patient demographics and comorbidities, operative characteristics, and 30-day complications were recorded. Multivariate analyses were performed to determine predictors of transfusion as well as the effect of transfusion volume on 30-day complication rates. A total of 1691 patients were included. Male sex (P = 0.010), esophageal or gastrointestinal disease (P = 0.016), cardiac risk factors (P = 0.037), preoperative inotrope requirement (P = 0.031), total operative time of 300 minutes or more (P < 0.001), and posterior arthrodesis of 13 or more vertebral segments (P < 0.001) were independent risk factors for requiring blood transfusion. Total transfusion volume of 20 mL/kg or more was the minimum volume independently associated with increased rates of total complications (P = 0.018), with a complication rate of 5.9%. We present the first large, comprehensive analysis of complications related to blood transfusion events and transfusion volume on short-term postoperative complications after posterior arthrodesis for AIS. Although transfusion in general is not associated with 30-day adverse events, a volume of 20 mL/kg was associated with higher complication rates. 4.